Multiple fiber Bragg grating sensing system based on active mode-locking fiber laser - Meng, Delong; Yu, Xiaolei; Zhao, Zhimin; Shan, Shilei; Li, Hongzhe (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
In this paper, a new multiple fiber Bragg grating (FBG) sensing system based on active mode-locking fiber laser is proposed. The active mode-locking fiber laser is composed of a linear cavity with an Fabry–Perot laser diode (F-P LD) as a reflective cavity mirror, and the erbium-doped fiber as the gain medium. Meanwhile, the F-P LD is also used as the modulating element of the fiber laser. Multiple FBGs cascaded in a long fiber are used as both the sensors in the system and the components for wavelength selection in the active mode-locking fiber laser. The capacity of the proposed sensing system to interrogate multiple FBGs in wavelength and spatial domain is investigated. The proposed sensing system has the characteristics of low cost, good stability, good compatibility, and can be used in quasi-distributed multi-point sensing.
Optica Applicata, Vol. 52, 2022, nr 3, s. 375-384
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; fiber optics; Fabry–Perot laser diode; fiber laser; active mode-locking; fiber Bragg grating